PERENCANAAN SALURAN SEKUNDER D.I MANINJAU KECAMATAN PANTI KABUPATEN PASAMAN - Jefrianto Jefrianto; Surya Eka Priana; Selpa Dewi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Pasaman Regency is one of the regencies in West Sumatra Province, the capital of Pasaman Regency is located in Lubuk Attitude. This district has an area of 3,947.63 km2 and a population of 253,299 according to the 2010 population census and 301,444 people in 2021 with a government covering 12 sub-districts and 37 Nagari. Geographically, Pasaman Regency is crossed by the equator and is located at 0°55' North Latitude to 0°6' South Latitude and 99°45' to 100°21' East Longitude. The Maninjau area of Panti sub-district has an agricultural area of 200 ha. Regency by using primary and secondary data collection and using rainfall data for the last 10 years. data processing using the harsper and gumbel methods. From the results of the calculation of the channel planning dimensions, the calculation results where the Q value is 4.44 m³/sec is greater than the Qmax value 3.90 m³/s from the calculation results using the Gumbel method for R 5TH is 334 mm and The results of calculations using the Haspers method with a Q value of 3.90 m³/sec. The results of the study can be used as input and reference for planning irrigation needs in the future. the results of this research on irrigation can provide the greatest benefit to the community, and the purpose of this irrigation itself can be achieved and beneficial as optimally as possible.Keywords: Channel Dimensions, Water discharge rainfall, HaspersMethood, Gumbel Method, Secondary Channel